Angka kejadian dan gambaran klinikopatologi kanker rongga mulut di Bali pada periode januari 2015 – oktober 2016 - Damayanti, Tiara Awidia; Setiawan, I Gede Budhi (E-Jurnal Medika Udayana; Vol 7 No 2 (2018): E-Jurnal Medika Udayana, 2018)
Head and neck cancer is a serious problem and the most common cancer in the world. Oral cancer that belongs to this group, is in the top position of six types most common malignancies in Asia. Malignancies of the oral cavity often rarely detected. This study was conducted to determine the incidence and clinicopathological patterns as well as the distribution of oral cancer in Bali based on several characteristics. Descriptive method with cross-sectional design using secondary data from patient’s medical records in Sanglah Hospital and Cancer Registry of PERABOI in Bali. Samples are collected with the criteria of patients who first diagnosed with oral cancer in the period January 2015-October 2016. Based on the data obtained from Sanglah Hospital and Cancer Registry of PERABOI, 90 samples of oral cancer were obtained. Furthermore, the results show that of the 90 samples: thirty-five samples are tongue as the location of primary tumor; thirty-six samples are stage IVA with thirty-four samples of tumor that invades adjacent structures (T4a), thirty-seven samples with no regional lymph nodes metastasis (N0) and sixty-seven samples of no distant metastasis (M0); thirty-two samples with well differentiated tumor (grade I); sixty-nine samples of squamous cell carcinoma histopathological type. The incidence of oral cancer in Bali in the period of January 2015–October 2016 was 90 cases with the most common characteristics: tongue is the most common location of primary tumor, stadium IVA, T4a, N0, M0, grade I and squamous cell carcinoma histopathological type. Keywords: location of primary tumor, TNM, stage, grade, histopathological type